Cavitation : a conference arranged by the Fluid Machinery Group of the Institution of Mechanical Engineers, Herriot-Watt University, Edinburgh, September 3-5, 1974 - Institution of Mechanical Engineers (Great Britain). Fluid Machinery Group (London : Mechanical Engineering Pub., 1976)
07